1993
DOI: 10.1002/art.1780361118
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of borrelia burgdorferi in ligamentous tissue from a patient with chronic lyme borreliosis

Abstract: Objective. To document the persistence of Borreliu burgdorferi in ligamentous tissue samples obtained from a woman with chronic Lyme borreliosis.Methods. Spirochetes were isolated from samples of ligamentous tissue, and the spirochetes were characterized antigenetically and by molecular biology techniques. The ligamentous tissue was examined by electron microscopy. Humoral and cellular immune responses were analyzed.Results. Choroiditis was the first recognized manifestation of Lyme disease in this patient. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 19 publications
3
90
0
3
Order By: Relevance
“…B. burgdorferi organisms contain several surface molecules that facilitate binding to proteoglycan components of the extracellular matrix of synovial tissues. Indeed, B. burgdorferi organisms have been shown to persist in the connective tissues of chronically in-fected mice and humans (10,11,67). The presence of spirochetes at these sites is likely required for the inflammatory response leading to arthritis in individuals not receiving antimicrobial therapy.…”
Section: Development Of Arthritis Upon Infection With B Burgdorferimentioning
confidence: 99%
“…B. burgdorferi organisms contain several surface molecules that facilitate binding to proteoglycan components of the extracellular matrix of synovial tissues. Indeed, B. burgdorferi organisms have been shown to persist in the connective tissues of chronically in-fected mice and humans (10,11,67). The presence of spirochetes at these sites is likely required for the inflammatory response leading to arthritis in individuals not receiving antimicrobial therapy.…”
Section: Development Of Arthritis Upon Infection With B Burgdorferimentioning
confidence: 99%
“…Although isolation of spirochetes from cardiac tissue (6, 7) and synovium (8,9) of human patients clearly establish that inflammation is triggered by infection, other host factors clearly regulate the severity and longevity of disease. Early studies revealed high concentrations of proinflammatory cytokines IL-1 (10), IL-6 (11), and TNF-␣ (12,13).…”
mentioning
confidence: 99%
“…The ability of spirochetes to embed themselves in dense collagen bundles may offer protection from both antibodies and antibiotics. [52][53][54][55] Putting all this information together, we can speculate that CD14 not only helps in the activation of MMP-9 necessary for degradation of existing collagen but also may limit the continued production of collagen. Control of these fibrotic processes by CD14 not only leads to higher neutrophil recruitment and clearance of spirochetes but also deprives B. burgdorferi of "hide-outs" within joints.…”
Section: Discussionmentioning
confidence: 98%